2011
DOI: 10.1103/physrevb.83.220403
|View full text |Cite
|
Sign up to set email alerts
|

Long-range magnetic ordering in Na2IrO3

Abstract: We report a combined experimental and theoretical investigation of the magnetic structure of the honeycomb lattice magnet Na2IrO3, a strong candidate for a realization of a gapless spin-liquid. Using resonant x-ray magnetic scattering at the Ir L3-edge, we find 3D long range antiferromagnetic order below TN =13.3 K. From the azimuthal dependence of the magnetic Bragg peak, the ordered moment is determined to be predominantly along the a-axis. Combining the experimental data with first principles calculations, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

29
393
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(426 citation statements)
references
References 20 publications
29
393
0
4
Order By: Relevance
“…The zigzag AFM order was found in experiments for the iridates [6][7][8][9]. This zig-zag order phase in the phase diagram appears in the third quarter of Fig.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…The zigzag AFM order was found in experiments for the iridates [6][7][8][9]. This zig-zag order phase in the phase diagram appears in the third quarter of Fig.…”
mentioning
confidence: 82%
“…A phase transition from a stripy antiferromagnetic(AFM) order to the Kitaev SL phase was predicted. Experiments for the iridates, however, found a zig-zag AFM order [6][7][8][9]. These progresses drive a number of further researches [10][11][12][13][14][15][16][17][18].…”
mentioning
confidence: 99%
“…13 This lattice effect is further evidenced from studies of Ru 1−x Ta x Sr 2 Nd 0.95 Y 0. 15 Ce 0.9 Cu 2 O 10 materials; MR 9T (4 K) increases from − 28% to − 49% as x increases from 0 to 0.2, which further expands the unit cell. 12 In an attempt to broaden this library of layered cuprates and search for further novel properties, we have experimented with the substitution of alternative transition metals into the 1222-layered structure.…”
Section: Introductionmentioning
confidence: 99%
“…Even so, the Kitaev spin liquid in honeycomb iridates has not been observed yet; in both Na 2 IrO 3 and Li 2 IrO 3 , magnetic order has been observed at low temperatures. [7][8][9] Moreover for Na 2 IrO 3 , the KH model in its original form does not appear to be sufficient to account for neither the zigzag magnetic order nor the spectrum of magnetic excitations that have been measured in neutron scattering experiments. 8,9,11 To explain the experimental observations in Na 2 IrO 3 , three different modifications of the super-exchange model have been proposed.…”
mentioning
confidence: 99%
“…Recently, Jackeli and Khaliullin 1 suggested that the Kitaev model could actually be realized within the honeycomb iridates with general formula A 2 IrO 3 , since the anisotropic part of the interactions among Ir-ions has the same form as the Kitaev coupling. This suggestion has triggered a lot of experimental [7][8][9][10][11] and theoretical [12][13][14][15][16][17][18] activity in the study of Na 2 IrO 3 and Li 2 IrO 3 compounds.…”
mentioning
confidence: 99%